Sturge-Weber syndrome with a partially enhanced choroid plexus on follow-up MRI: A case report - Visrutaratna P. (2014)
A 3-year and 6-month old girl diagnosed as having Sturge-Weber syndrome had a follow-up magnetic resonance (MR) imaging, which showed right cerebral atrophy with cortical calcification. The choroid plexus was enlarged but partially enhanced, although it had been homogeneously enhanced on the first MR imaging when she was five days old. Abnormal choroid plexuses in patients with Sturge-Weber syndrome may not be static and may be related to the age of the patients when imaging is done.